Improving the Order Processing Procedure at Phu Hoa An Import-Export Textile Garment Company. - Dang, Duc Minh Nhat (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Logistics and Digital Supply Chain Management; 2021-2025.